A Cross Sectional Study to Calculate the Rate of Stigma Against Mental Illness Amongst the Post Graduate Trainees (PGT) of Different Departments in a Tertiary Care Hospital - Jogezai, Nazo Wazir; Khatoon, Haleema; Minhas, Fareed A. (Journal of Pakistan Psychiatric Society, 2016)
Abstract